Helical Blade Versus Screw Fixation in the Treatment of Hip Fractures With Cephalomedullary Devices: Incidence of Failure and Atypical "Medial Cutout". Issue 8 (August 2018) - Chapman, Talia; Zmistowski, Benjamin; Krieg, James; Stake, Seth; Jones, Christopher M.; Levicoff, Eric
Abstract : Objective: To evaluate the rates and mechanisms of failure for cephalomedullary nail fixation using helical blade versus screw fixation and to identify the predictors of failure. Design: Retrospective study. Setting: Community teaching hospital. Patients/Participants: A total of 126 patients were treated with cephalomedullary fixation for low-energy hip fractures. Intervention: All procedures used the Trochanteric Fixation Nail (Synthes) with either a helical blade [71 (56.3%)] or screw [55 (43.7%)]. Main Outcome Measurements: Failures, defined by nonunion, hardware cutout, and need for revision surgery were independently reviewed by a fellowship-trained orthopaedic trauma surgeon for an assessment of reduction quality and hardware placement. Results: Seven failures of fixation (5.6%) occurred, all of which used a helical blade. Five failures resulted from medial migration of the helical blade through the femoral head, whereas 2 resulted from typical superolateral cutout and varus collapse. There was no difference in the average tip apex distance between the cases using blade versus screw fixation or between failures and the remainder of the cohort. Basicervical fractures had a significantly higher rate of failure than other fracture patterns. Conclusions: This study showed a higher failure rate with use of the blade and supports the use of screw fixation in these fractures. In addition, we confirm an atypical mode of failure, lateral migration of the femoral head with protrusion of the helical blade, which contributes significantly to the overall failure rate of this implant and occurs despite appropriate fracture reduction and hardware placement. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.